EVALUASI SEDIAAN SABUN CAIR DARI EKSTRAK KOPI ROBUSTA (Coffea canephora) - Maratu Soleha; Pricillya Maria L; Anfa Insan Pradito (Jurnal Farmasi IKIFA, 2024)
Indonesian natural ingredients have been known to have various benefits in the health sector and have been formulated in various dosage forms, one of which is topical preparations. Previous research has shown the benefits of plants such as binahong leaves that can be used as antibacterials and tomato fruit extracts as antioxidants. These plant materials have been made into active compounds in various topical preparations, one of which is liquid soap. The purpose of this study was to determine the results of the evaluation of liquid soap preparations from robusta coffee extract (Coffea canephora) produced to meet SNI requirements. This research is a quantitative descriptive study. The population in this study were robusta coffee plants (Coffea canephora). The sample in this study was Lampung Sumatra robusta coffee obtained from Pasar Santa, South Jakarta. The thick extract used in this study was obtained by maceration method. The robusta coffee extract liquid soap preparation consists of F1 as much as 2 g and F2 as much as 4 g. Evaluation carried out at week 0 showed organoleptical results of liquid and thick brown color and typical coffee odor. The pH test results on F1 and F2 showed pH results of 9.2 and 9.2 which met the SNI requirements of around 8-11. Specific gravity test on F1 and F2 showed results of 1.0122 and 1.0131 g/mL which meet SNI requirements of around 1.01-1.10 g/mL. viscosity test on F1 and F2 showed results of 2416 and 2616 cps which meet the requirements of around 400-4000cps. The foam test on F1 and F2 showed results of 8.4 and 8.2 cm which met the requirements of about 1.3-22 cm. The displaced volume test on F1 and F2 showed results of 97 and 97 mL which met the requirements of not less than 95 mL. From the results of the study, it was concluded that the liquid soap preparation from robusta coffee extract (Coffea canephora) carried out in week 0, namely the organoleptical test, pH test, specific gravity test, viscosity test, foam test and volume moved test met the SNI requirements